Pierwsze opisy podróży Polaków do Ziemi Świętej – wprowadzenie do badań w ujęciu geopoetyki - Katarzyna Ossowska (Meluzyna: dawna literatura i kultura, 2014)
The article presents the 15th and 16th century accounts on the journeys of Poles to the HolyLand, including Chorografia abo topografia, to jest osobliwe a okólne opisanie Ziemie Świętej byAnzelm Polak (15/16th century), Terminatio ex itinerario Magnifici Domini Ioannis Comitis inTarnów… by Jan Tarnowski (1488–1566), Peregrynacja do Ziemi Świętej by Jan Gorynski (16thcentury) and Podróż do Ziemi Świętej, Syrii i Egiptu by Mikołaj Krzysztof Radziwiłł (“Sierotka”)(1549–1616). The article mentions as well a little known work Peregrinatio ad Terram Sanctamby Johannes Poloner (15th century).Till now, the articles have been discussed separately, in literary or religious contexts. However,due to an increasing interest in the geopoetics, it is beneficial to look at all accounts on journeysto the Holy Land collectively and through them get to know about the lands along the coast ofthe Mediterranean Sea, connecting Syria and Egypt.The aim of this article is to present the arguments confirming the legitimacy of the use of geopoeticsin the analysis of old texts. Moreover, the article points out to the issues discussed furtherin the thesis, e.g. the development of “description” in Polish literary tradition being one oftwo basic narrative elements.